Implementation of Learning Assistance to Chemistry Learning Motivation of Students in MAN 4 Sleman - Artina Diniaty; Lina Fauzi'ah (Universitas Islam Indonesia, 2019)
This study aims to determine the implementation of chemical learning assistance to students' learning motivation. Assistance efforts are carried out by managing the laboratory so that it can be used as a chemistry learning infrastructure, implementation, and discussion of tryout questions of SBMPTN along with the tricks to do them. In addition, chemedutainment is also carried out to motivate students to learn chemistry. The results showed that there were no significant differences in students' learning motivation through the implementation of chemical learning assistance. The implementation of chemical learning assistance needs to be carried out regularly and continuously in order to increase students' learning motivation.